Disability among lung cancer patients and its predictors: a cross-sectional study in a tertiary care centre at Kolkata, India - Pal, Jayita; Santra, Avradip (International Journal of Research in Medical Sciences, 2019)
Background: Lung cancer is one of the commonest cancer worldwide and also in India. Being a chronic disease, it is expected to result in disability during the course of the illness. Disability in turn results in deterioration of mental health and leads to poor quality of life. The present study intended to assess the degree of disability among lung cancer patients and to find out the covariates of the same. Methods: An institution based cross-sectional study had been conducted over a period of six months among lung cancer patients attending a tertiary care centre. Exit interview had been conducted with a pretested schedule after taking informed consent. Disability had been assessed by WHO Disability Assessment Schedule 2.0 (WHODAS 2.0). Data were entered and analysed in SPSS 20.0 version. Results: A total of 210 patients were recruited in this study. Half of the study population were suffering from higher level of disability. Multivariate analysis revealed degree of disability was higher among the patients who were financially dependent to others, had advanced stage of the disease and when time since diagnosis was more than one month. Conclusions: Holistic approach needs to be taken up to address this alarming issue of disability and its consequences among lung cancer patients. The approach should include various rehabilitative measures, social security schemes by the government and active involvement of non-governmental organisations.